The economic value of knowing BRCA status: BRCA testing for optimizing treatment in recurrent epithelial ovarian cancer. (16th March 2023) - Oh, Mok; McBride, Ali; Bhattacharjee, Sandipan; Slack, Marion; Jeter, Joanne; Abraham, Ivo
ABSTRACT: Background: This study aimed to estimate the incremental lifetime effects, costs, and net monetary benefit (NMB) of knowing BRCA information for recurrent ovarian cancer (ROC) patients in a given year and the cumulative savings of yearly hypothetical cohort testing over 16 years. We compared two strategies: (1) 'with BRCA information' and (2) 'without BRCA information.' Methods: Incremental NMB (INMB) was calculated as the average net monetized benefit of knowing BRCA status. The net monetized value (cumulative INMB) of knowing BRCA information was estimated by multiplying the INMB with the eligible ROC patients in year 2020 and extended for potential ROC patients over 16 yearly hypothetical cohorts of ROC patients Results: Knowing BRCA information for ROC patients provided an additional monetized value of $3, 528 in (payer) and $3, 194 (society). Escalated to all ROC patients in the U.S. and future incidence ROC estimates, knowing BRCA information resulted in a lifetime cumulative INMB of $35.6 million (payer) and $32.2 million (society) for the 2020 cohort; and yielded an accumulated value of $97.3 million (payer) and $88.0 million (society) over 16 yearly hypothetical cohorts of ROC patients Conclusions: The economic value of knowing BRCA status of all U.S. ROC patients provides short-term and long-term evidence for optimizing treatment